2015
DOI: 10.1021/es504684x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Shortcut Estimation Method for Regeneration Energy of Amine Solvents in an Absorption-Based Carbon Capture Process

Abstract: Among various CO2 capture processes, the aqueous amine-based absorption process is considered the most promising for near-term deployment. However, the performance evaluation of newly developed solvents still requires complex and time-consuming procedures, such as pilot plant tests or the development of a rigorous simulator. Absence of accurate and simple calculation methods for the energy performance at an early stage of process development has lengthened and increased expense of the development of economical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(70 citation statements)
references
References 22 publications
6
62
0
Order By: Relevance
“…8. The regeneration energy penalty (Q Regen ) of the saturated MEA solution (0.34 mol CO 2 /mol IL) was found to be 3.77 GJton -1 CO 2 , and the largest two contributions were the desorption reaction heat (Q des ) used to disrupt the CO 2 -absorbent bonding product and the latent heat of vaporization (Q latent ) during the regeneration process, which was highly inconsistent with the reference data (Kim et al 2015). The water content of the [TETAH][Lys]-water system was higher than that of the MEA solution, and the water presented a heat capacity that is significantly higher than that of the other components (ethanol, lysine, TETA, etc.…”
Section: Thermodynamics Analysismentioning
confidence: 72%
See 1 more Smart Citation
“…8. The regeneration energy penalty (Q Regen ) of the saturated MEA solution (0.34 mol CO 2 /mol IL) was found to be 3.77 GJton -1 CO 2 , and the largest two contributions were the desorption reaction heat (Q des ) used to disrupt the CO 2 -absorbent bonding product and the latent heat of vaporization (Q latent ) during the regeneration process, which was highly inconsistent with the reference data (Kim et al 2015). The water content of the [TETAH][Lys]-water system was higher than that of the MEA solution, and the water presented a heat capacity that is significantly higher than that of the other components (ethanol, lysine, TETA, etc.…”
Section: Thermodynamics Analysismentioning
confidence: 72%
“…Energy requirement for the biphasic solvent regeneration. The data of MEA was obtained from Kim et al(Kim et al 2015) The specific solvent loss of various absorbents regenerated at 120°C…”
mentioning
confidence: 99%
“…When CO2 is absorbed in the solution of MEA, DEA, and MDEA, the following reactions take place. For MEA, where R represents the functional group [8,12].…”
Section: Alkanolamine Solvents and Reaction Mechanismmentioning
confidence: 99%
“…The world's most proficient coal control plants, for example, the John W. Turk plant in Arkansas and the Isogo Thermal Power Station in Japan show that taking care of developing electric demand cost-successfully can be adjusted with natural and manageability goals. These power plants depend on ultra-supercritical coal innovation, which produces high steam temperatures and weights, empowering them to be more effective at changing over warm vitality into electrical yield [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…DEA-12-PD and 12-HEPP were among the tested solvent candidates. Knuutila et al (2019) [3] tested DEA-12-PD and 12-HEPP promoted with primary amines and showed that by using a short cut method [16], the tested solvent blends could be regenerated with reboiler duties 2.5-2.6 MJ/kg CO 2 . These values are similar to those values measured with several novel solvent blends, 2.5-3.0 MJ/kg CO 2 [17][18][19].…”
Section: Introductionmentioning
confidence: 99%